Association of Neutrophil–Lymphocyte Ratio and the Presence of Noncalcified or Mixed Coronary Atherosclerotic Plaques. (March 2018) - Li, Tiewei; Gu, Chun; Wang, Fang; Lv, Bin; Zhang, Changlin; Peng, Rui; Cong, Xiangfeng; Chen, Xi
The neutrophil–lymphocyte ratio (NLR) is an emerging cardiovascular risk factor. Patients with mixed plaques (MPs) or noncalcified plaques (NCPs) have a higher risk of poor outcomes. However, there are few published data on the relationship between the NLR and the presence of NCP or MP (NCP/MP). We retrospectively collected the clinical and laboratory data of 598 patients with chest pain. According to whether they had coronary atherosclerotic plaques and the characteristics of the most stenotic plaque, we divided them into no plaque, calcified plaques, NCP, and MP. Those with NCP/MP had significantly elevated neutrophil count and NLR ( P < .05). The proportion of NCP/MP was significantly increased from 28.6% in the NLR < 1.55 to 42.7% in the NLR > 2.21 group ( P = .013). Multiple logistic regression analysis showed that NLR was an independent risk factor for the presence of NCP/MP (odds ratio = 1.195; 95% CI: 1.020-1.400; P = .028). The present study demonstrated that the NLR was independently associated with the presence of NCP/MP.